PENGOLAHAN AIR LIMBAH PENCUCIAN RUMPUT LAUT UNTUK MENURUNKAN NILAI BOD DENGAN SISTEM BIOFILTRASI EKOSISTEM (SBE) - Sudyadnyana Sandhika, I M. G.; Budiarsa Suyasa, I W.; Suprihatin, Iryanti Eka (Jurnal Kimia (Journal of Chemistry), 2013)
The research about treatment of wastewater from seaweed washing by biofiltration system with and without microorganism enrichment has been carried out. This research aims to determine the minimum time of the biofiltration process to decrease the BOD to meet the quality standard and the capacity of the biofiltration system. The results showed that the minimum contact time to meet the quality standard (75 mg/L) for BOD is 40 hours for both system. Treatment capacities of the biofiltration system without addition of microorganisms for BOD is 6,8056 mg/L/m 3 hours, whereas the treatment capacities of the system with addition of microorganisms is 6,4965 mg/L/m 3 hours.
Keywords: Biofiltration, Seaweed washing effluent, and BOD